Propuesta de plan de mejoras para el balneario eco turistico coco viche, que incide en el desarrollo turístico local. - Puchaicela Caraguay, Veronica Leonor (2017)
The present project contains reliable and reliable information of an entrepreneurial and social nature based on the empirical and theoretical study in order to identify business niches taking advantage of an organizational and individual development option. The project is carried out under the research lines of the Technical University of Machala as integral management of entrepreneurship, this line focuses its interest in the approach of the entrepreneurial cycle and its related variables. The intention is to be able to explain the conditioning agents of the differential behavior of the entrepreneurial process, opting as the main axis of the Entrepreneurship Evaluation, which was the basis for the design of an improvement plan for the eco-tourism center "Coco Viche", with the aim of improving The situation in which it is, solving an existing need or problem as well as identifying the respective design of the necessary conditions for its optimal solution, the same that consists of physical and human restructuring of this spa, which is located in the neighborhood called Its same name. This improvement plan aims to increase the number of tourists in the area, providing services related to distraction and family coexistence surpassing the expectations of visitors, and at the same time obtain better socioeconomic benefits, in a peaceful environment and surrounded by landscapes Natural like the sea, the beach and others. The first chapter describes the business idea and has also defined certain important terms for the development of this project as the description of the business idea, theoretical basis of the business idea and the market study, in order to That serves for a better understanding of it and as a source of consultation for those who wish to know a little more about a tourism project. The second chapter describes in detail the organizational design of the enterprise as well as the description of the entrepreneurship, managerial foundation of the enterprise and the organizational and functional structure as it is constituted the resort “Coco Viche”, which services currently offer, who are at the forefront Of this ecotourism center, also indicates which are its main competitors, and their respective analysis with respect to them. In the third chapter you can find out what services are offered, and what services will be offered as a value proposition after the implementation of the improvement plan, what your target market is, and how the market will be segmented , It also indicates the marketing channels, customer relations, income sources, assets for the operation of the business, business activities, network of partners and cost structure, which will be given for the positioning of the place in the And the strategic alliances that will be used to achieve the proposed objectives. Finally, the fourth chapter will be composed of the economic, operational and financial analyzes that have been done with respect to this project, which determined the economic and financial viability of the project and its environmental and social impacts in the implementation of this improvement plan .